Drivers and impacts of mobile phone-mediated scaling of agricultural technologies: A meta-analysis - Gouroubera, Mori W.; Adechian, Soulé Akinhola; Segnon, Alcade C.; Moumouni-Moussa, Ismail; Zougmore, Robert B. (Frontiers Media, 2025)
Mobile phone-mediated scaling of agricultural technologies (MPSATs) attracts attention as an effective approach for promoting agricultural development and sustainability. Despite the growing interest, a comprehensive understanding of drivers of MPSAT at the farm level and the evidence base of their impacts remains limited. To fill this gap, we conducted a systematic literature review and meta-analysis of 18 relevant empirical studies covering 10,757 farmers across 12 countries. Meta-analyses reveal that farmers’ innovativeness and full-time farming increase the odds of adopting agricultural technologies. Age, gender, digital skills, mobile phone device ownership, and membership in farmer groups also influence MPSAT but display heterogeneity. Moderation analysis reveals that the development status of countries plays a moderating role in variables such as asset ownership and farm size. Moreover, the results show that using mobile phones as a standalone method increases the odds of adopting agricultural technologies by 2%. In combination with traditional extension methods, this figure rises significantly to 17%. Additionally, MPSAT increases yields by 2%, and profits by 5%, and contributes to a 3% improvement in farmers’ learning outcomes. This study sheds light on the potential and multifaceted nature of MPSAT, providing insights for policymakers and practitioners promoting sustainable agriculture through digital technologies.